2016
DOI: 10.1152/japplphysiol.00805.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Gifford et al.: Symmorphosis in chronic heart failure patients?

Abstract: TO THE EDITOR: We thank Gifford and colleagues for their comment (3) and agree that the correlation between mitochondrial oxidative capacity and V O 2 max among our chronic heart failure (CHF) patients is not significant [r ϭ 0.47, P ϭ 0.11 (5)]. However, we disagree with their conclusion that the slope is "effectively 0/1" and that V O 2 max and mitochondrial oxidative capacity are dissociated in CHF patients. The fact that significance was not reached in this subgroup may also be due to insufficient statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Some of these adaptations to training take place despite what appears to be an already adequate capability. For example, it has been reported that mitochondrial respiratory function exceeds oxygen delivery in humans, and is in excess of that required when half or more of the muscle mass is engaged during exercise (e.g., cycling, running) [30][31][32]. Nonetheless, mitochondrial respiratory function has been reported to increase following exercise training [20,33,34], as have both mitochondrial protein synthesis (MitoPS) [35] and mitochondrial content [1,18,36], whereas reductions have been reported following different types of detraining [1,27,37].…”
Section: Mitochondrial Adaptations To Exercise Trainingmentioning
confidence: 99%
“…Some of these adaptations to training take place despite what appears to be an already adequate capability. For example, it has been reported that mitochondrial respiratory function exceeds oxygen delivery in humans, and is in excess of that required when half or more of the muscle mass is engaged during exercise (e.g., cycling, running) [30][31][32]. Nonetheless, mitochondrial respiratory function has been reported to increase following exercise training [20,33,34], as have both mitochondrial protein synthesis (MitoPS) [35] and mitochondrial content [1,18,36], whereas reductions have been reported following different types of detraining [1,27,37].…”
Section: Mitochondrial Adaptations To Exercise Trainingmentioning
confidence: 99%